A novel study approach on Scutellaria altissima L. cultivated at the Ghirardi Botanic Garden (Lombardy, Italy). (12th October 2020) - Giuliani, C.; Bottoni, M.; Ascrizzi, R.; Santagostini, L.; Papini, A.; Flamini, G.; Fico, G.
Abstract: Within an Open Science project, research was carried out to describe to the public of the Ghirardi Botanic Garden (BS, Lombardy, Italy) the invisible features of plants. This work is dedicated to Scutellaria altissima L. ( Lamiaceae ). Micromorphological, histochemical and phytochemical investigations were conducted on the vegetative and reproductive organs to correlate the structures involved in the emission of substances and their unique productivity. This work reports volatile organic compound (VOC) profiles of leaves and flowers and the composition of essential oil (EO) obtained from aerial parts of plants cultivated in Italy that have never been described before. Three morphotypes of glandular trichomes were observed: peltate, short‐stalked capitate and long‐stalked capitate. Peltate trichomes were the main producers of terpenes, short‐stalked capitates of polysaccharides and long‐stalked capitates of terpenes and polyphenols. The leaf VOC profile showed heterogeneous composition, with non‐terpene derivatives as the major chemical class (71.04%), while monoterpene hydrocarbons represented almost the totality of the flower (99.73%). The leaf presented a higher number of total (37 versus 11) and exclusive (33 versus 7) compounds. ( Z )‐3‐Hexenol acetate was most abundant in the leaf and ( E )‐β‐ocimene in the flower. Four common compounds were detected: β‐pinene, β‐caryophyllene, γ‐muurolene and germacrene‐D. The EO contaied 21 compounds, dominated by β‐caryophyllene, linalool and hexahydrofarnesyl acetone. This research allowed us to correlate morphotypes of the secretory structures with the production of secondary metabolites, with the aim of providing the public of the Ghirardi Botanic Garden with a dedicated iconographic approach, which accounts for olfactory perception linked to S. altissima . Abstract : Two trichomes morphotypes, peltate and long‐stalked capitate, are responsible for the production of the most abundant terpenes, i.e. (Z)‐3‐Hexenol acetate in the foliar, (E)‐β‐ocimene in the floral VOC profile.